A Study of Devadūtasutta in Buddhist Scriptures - Kovito, Phra Phakawat (Mahachula Academic Journal, 2024)
The study consisted of the following objectives: 1) to investigate the background of Devadūtasutta; 2) to explore the Dhamma related to Devadūta; and 3) to analyze Devadūtasutta in Buddhist scriptures. The study used a documentary research technique, examining Buddhist scriptures and related materials. The study discovered that Devadūta refers to life's phenomena, including birth, old age, sickness, punishment, and death. One that engages in misconduct by body, speech, and mind will be reborn in hell after death. There the guard of hell will show him to King Yama, where he will be asked, “This person, didn’t you ever see among human brings a newborn baby, the elderly, the gravely ill, the criminal, the dead?” If he replies “Yes, I have seen this, and I contempled it upon myself,” he will then be freed from hell. But, if he replies “Yes, I have seen this, but I never contemplates it upon myself,” he will be put in hell. The Dhamma related to Devadūta is non-negligence through thorough reflection on birth, old age, sickness, punishment, and death. One should then take it upon themselves and do good by body, words, and mind, while also understanding the law of cause (kamma) and effect (vipaka). The Dhamma that is against Devadūta is negligence, resulting in decrease and unpleasantness. Devadūta has two points of view, which are: (1) seeing Devadūta and realizing the sense of urgency to do good by body, words and mind, while developing oneself according to the four noble truths (ariyasacca), and contemplating on the impermanance, suffering and non-self. Finally, one should also use wisdom to contemplate on oneself and practice meditation in order to be liberated from the wheel of rebirths and lead a happy life; and (2) seeing Devadūta and having craving, greed, hatred, delusion, and suffering. Devadūta is the reason for the creation of the literature on Phra Malai, who bestows mercy to hell creatures.